PERANCANGAN MEDIA IKLAN BATIK SURABAYA SEBAGAI UPAYA MEMPERKENALKAN PRODUK BUDAYA LOKAL - Kurniasari, Annisa Tiara (Jurnal Art Nouveau, 2014)
Abstract: Surabaya as the largest trading city in East Java has a cultural heritage that is worth the Surabaya Batik. Surabaya Batik is characterized as the use of bright colors with motifs based on the legend and the origin of the city of Surabaya. But not a lot of people in Surabaya itself is aware of the existence of batik Surabaya. Therefore, it needs a medium in order to accommodate all the information about batik Surabaya to introduce local cultural products. The design using observation, interview, literature, and documentation. The concept is used to direct the design of the media is